Interpretación del mecanismo fisiopatogénico de la psoriasis Interpretation about physiopathogenic mechanism of psoriasis - RL Panzeri (Asociación Argentina de Dermatología, 2009)
La psoriasis es una enfermedad de base inmuno-genética, que se acompaña de enigmas en el compromiso genético, la compleja red bioquímica de interleuquinas participantes, la interacción de las moléculas de adhesión, el rol definitivo de las células involucradas: célula de Langerhans, linfocitos, queratinocitos, mastocitos y neutrófilos, en el sistema de señalización intercelular, el condicionamiento biológico del paciente vulnerable y en el rol dominante del stress, como factor desencadenante a través de la liberación de neuropéptidos. Todos estos enigmas se irán develando en el devenir del avance de los constantes estudios, que se realizan sobre esta dinámica enfermedad. The physiopathogenic mechanism of psoriasis continues representing a challenge for dermatologists, immunologists and molecular biologists; trying to discover the biochemical primary alteration and the set of immunological events on that they put in march for her clinical expression. Up to the present it is of unknown reason. It is defines as an inflammatory chronic disease that compromises dominant the skin, being characterized by papules and erythematic-scaly plates. The genetic factor is indispensable in order that the individual falls ill with psoriasis, but not sufficiently. A fault must exist in his immune system, without which the disease would not express either. An intrinsic aberration exists in the skin of the vulnerable patients. The genetic determinism, the deregulation and activation of the immune system with the subsequent waterfall of inflammatory half-full events for cytokines would be the base to interpret and to understand the development of the psoriasis.